ON THE APPLICABILITY OF THE UTI POSSIDETIS JURIS PRINCIPLE DURING DELIMITATION OF THE CASPIAN SEA AMONG THE LITTORAL STATES - HUMBATOV, Fuad (CENTRAL ASIA AND THE CAUCASUS, 2009)
One of the Caspian region’s most problematic issues is determining the legal status of the Caspian Sea. The status of the Caspian Sea was first enforced in two agreements entered between Russia and Iran in 1921 and 1940. But the collapse of the U.S.S.R. and, as a result, the appearance of newly independent states on the Caspian coast (Azerbaijan, Kazakhstan, and Turkmenistan) led to a change in the existing legal, as well as political, positions in the region. This was partially reflected in U.N. documents.1 The regime established as early as Soviet times no longer met the interests of the littoral states, particularly with respect to use of the economic resources of the Caspian’s seabed and its contiguous waters, which made re-examination of the issue obligatory. At present, the countries of the region are divided on this issue, upholding two radically opposing viewpoints. Iran’s position, and to some extent Russia’s, is based on the fact that the Caspian Sea is a lake, the legal status of which was defined by the agreements of 1921 and 1940 which should be considered valid until new agreements are entered on this issue (the condominium thesis). However, the new littoral states (Azerbaijan, Kazakhstan, and to a lesser extent Turkmenistan) refer to the legal mechanisms of territorial inheritance of the states based on the so-called uti possidetis, ita possideatis principle (as you possess, so may you possess), that is, the principle of succession of territories and boundaries.2 It enforces the state’s right to inherit the administrative borders they held at the time the colonial or totalitarian predecessor state collapsed. In this article, we shall try to offer a legal analysis of the two above-mentioned positions, as well as examine the applicability of the uti possidetis juris principle to the littoral states.